1999
DOI: 10.1073/pnas.96.9.5129
|View full text |Cite|
|
Sign up to set email alerts
|

Conservation of sequence and structure flanking the mouse and human β-globin loci: The β-globin genes are embedded within an array of odorant receptor genes

Abstract: Genetics. In the article "Conservation of sequence and structure flanking the mouse and human ␤-globin loci: The ␤-globin genes are embedded within an array of odorant receptor genes" by Michael Bulger, J. Hikke von Doorninck, Noriko Saitoh, Agnes Telling, Catherine Farrell, M. A. Bender, Gary Felsenfeld, Richard Axel, and Mark Groudine, which appeared in number 9, April 27, 1999 of Proc. Natl. Acad. Sci. USA (96,(5129)(5130)(5131)(5132)(5133)(5134), the authors request that the following change be noted. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 42 publications
7
102
0
6
Order By: Relevance
“…In addition, a 1-kb block of sequence located 3Ј of the globin genes also demonstrated significant homology with a similarly placed sequence in human (Fig. 3D), which corresponds to a nuclease hypersensitive site in erythroid cells (19,30). Along with the sequence matches within the introns, noncoding exons, and promoters of the ORGs, all of these regions are candidates for regulatory sequences.…”
Section: Sequence Alignments Between Human and Mouse In The Org-hbbcmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, a 1-kb block of sequence located 3Ј of the globin genes also demonstrated significant homology with a similarly placed sequence in human (Fig. 3D), which corresponds to a nuclease hypersensitive site in erythroid cells (19,30). Along with the sequence matches within the introns, noncoding exons, and promoters of the ORGs, all of these regions are candidates for regulatory sequences.…”
Section: Sequence Alignments Between Human and Mouse In The Org-hbbcmentioning
confidence: 83%
“…Our initial sequencing of regions flanking the HBBC locus in human and Hbbc in mouse demonstrated that the ␤-globin genes were embedded in a cluster of ORGs (19). We have extended our sequencing to include additional regions flanking the ␤-globin genes, which allowed us to generate a contiguous sequence of 224 kb from mouse and two contigs from human of 345 kb and 36 kb, separated by a gap of about 6 kb (Fig.…”
Section: Dna Sequence Of Hbbc and Surrounding Orgsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the absence of high GC content in cold-blooded vertebrates, when DNA probes of GC-rich, gene-rich sequences from chicken were hybridized to nuclei of a frog and a lizard, the homologous regions detected were found in central areas of the nuclei (Federico et al 2006). An increase in GC content in warm-blooded animals could confer a selective advantage particularly in genes which are expressed in many different cell types while a selective advantage may be lower or absent for genes which are functionally important only in one cell type such as the β-globin gene or the neighboring olfactory receptor genes (Bulger et al 1999). This may be one reason why the correlation of GC content and gene density is not perfect.…”
Section: Nuclear Positioning and Genomic Propertiesmentioning
confidence: 99%
“…The human α-actinin 2A isoform gene was amplified by PCR from pET6-ACTN2 (Young et al, 1998) with the α-actinin-EGFP fragment (Dätwyler et al, 2001), yielding the α-MHC-α-actinin-EGFP-IRES-BSD construct. The 523-bp DNase I-hypersensitive site (HS)-2 element (accession number: S73747.1) from the β-globin Locus Control Region (LCR) (Walters et al, 1996;Bulger et al, 1999;Grosveld, 1999) was amplified from mouse genomic DNA by PCR (primers: see Table 1), digested with MluI, and subcloned into the SM13.4 and FS2.2 vectors that contain an expression cassette for the α-actinin-EGFP fusion protein driven by the CMV-IE promoter and the 475-bp human elongation factor (EF)-1α promoter (Chung et al, 2002), respectively, yielding the HS2-CMV-α-actinin-EGFP and HS2-EF1-α-actinin-EGFP expression constructs. Finally, the HS2 fragment was also inserted upstream of the respective cardiac-specific promoters in bicistronic expression constructs.…”
Section: Gene Expression Vectorsmentioning
confidence: 99%